Social and Psychological Factors of the Compelled Choice of Profession - MIRONOVA, Oksana I.; PLUZHNIKOVA, Natalya I.; AKIMOVA, Natalya N.; NEKRASOVA, Marina V.; SHAGAEVA, Elena A.; ZHUKOVA, Valentina I. (Journal of Advanced Research in Law and Economics; Vol 5 No 2 (2014): JARLE Volume V, Issue 2(10), Winter 2014, 2017)
The article analyses the peculiarities of the compelled choice of profession. The results of empirical study revealed its social and psychological factors, in particular: ‘Continuation of a professional dynasty’, ‘Inaccessibility of training’, ‘Restrictions on health’, ‘Deficiency of professional kinds of activity in the place of residence’ and ‘A difficult life situation’. The psychological characteristic of each of the factors is disclosed. During the comparative analysis the gender and age-specific features of the compelled choice of profession are ascertained. Its interrelation with motivation to avoid failures and value orientations of the personality is defined.